Peran Social Provision dan Hope terhadap Community Resilience pada Penyintas Bencana Gempa Cianjur - Tessalonika Sembiring; O. Irene Prameswari Edwina; Serena Wijaya (Universitas Kristen Maranatha, 2026)
This study aims to examine the role of social provision and hope toward community resilience of survivors of the Cianjur earthquake. It was conducted with 135 survivors from five villages heavily affected by the earthquake. Data were collected using the Index of Perceived Community Resilience (IPCR) scale, the Adult Hope Scale (AHS), and the Social Provision Scale (SPS). Data analysis was performed using hierarchical multiple regression. The results show that social provision has a greater influence than hope in explaining community resilience. Although hope was significant in the initial model, but the effect becomes insignificant after taking social provision into account. These results highlight the importance of social factors in strengthening community resilience, particularly through supportive social relationships and access to aid in post-disaster contexts. Demographic factor (gender, age, education level and occupation) does not have a significant role toward community resilience of survivors of the Cianjur earthquake.